DEVELOPING WRITING SKILLS IN ENGLISH IN THE FIELD OF INTERNATIONAL LAW: LEGAL MEMORANDUMS, LETTERS, AND PETITIONS - Marfuakhon Akhmedova (Journals Park Publishing, 2024)
This study explores effective methods for enhancing writing skills in English within the domain of international law. Focusing on drafting legal memorandums, letters, and petitions, it emphasizes the importance of mastering formal style and textual structures. The article presenting relevant methodologies, a discussion on formal legal English, and practical recommendations. The findings underline the critical role of targeted training and structured exercises in fostering professional-level legal writing.
Keywords: Legal writing, international law, formal style, legal documents, legal memorandums, legal petitions, professional communication, legal English, writing structure, linguistic accuracy, legal terminology.